The conference of the birds - Attar, Farid al-Din, -approximately 1230.; Davis, Dick, 1945-; Darbandi, Afkham, 1948- (Harmondsworth : Penguin Books, 1984)
An allegorical poem about the search of the world's birds for the perfect king illustrates the mystical beliefs of sufism.
Translation of: Man{u4A71} al-{u4879}r.
'Biographical index': pages [230]-234.
Keywords: Sufi poetry; Sufi poetry, Persian; Sufism -- Early works to 1800